ANALISIS PERCEPATAN WAKTU TERHADAP BIAYA DENGAN METODE TIME COST TRADE OFF (Studi Kasus Proyek Pembangunan Gedung Islamic Center Kec. Rimbo Bujang Kab. Tebo Provinsi Jambi) - ., Taufiq; Nugroho, Meriana Wahyu; Yulianto, Totok; Sundari, Titin (Fakultas Teknik, Universitas Wiraraja, 2025)
Cost and time are critical factors in construction projects. Therefore, it is essential to determine the optimal cost and time by performing Crashing on activities within the critical path. The analysis begins by identifying the critical path using the Critical Path Method (CPM), followed by crashing the activities on the critical path. In this study, acceleration is achieved through three alternatives: adding 2 hours of overtime (alternative 1), increasing the workforce (alternative 2), and adding a night shift (alternative 3). The determination of the optimal cost and time is based on two key variablel cost and time utilizing Euclidean, analysis to identify the most efficient trade-off between the two.. The analysis reveals that the most optimal alternative is alternative 2 (increasing the workforce). The project's normal completion time is 210 calendar days with a cost of IDR 4,483,505,000 By applying Crashing, the project completion time is reduced to 148 calendar days, resulting in a time saving of 62 calendar days. However, this acceleration increases the cost to IDR 4,583,211,000 an additional IDR 99,705,000 Thus, alternative 2 is considered optimal compared to alternatives 1 and 3 in terms of cost and time.